[(AlxTi1−x)-(FeCoNi)12](AlxTi1−x)0.5Cr2.5 High-Entropy Alloy Coating by Laser Cladding - Shenghong Bo; Yaxiong Guo; Qibin Liu (Metals, 2022)
To prolong the service life of the stirrer impeller made by SUS 904L austenitic super-stainless steel, a series of [(AlxTi1−x)-(FeCoNi)12](AlxTi1−x)0.5Cr2.5 high-entropy alloy (HEA) compositions were designed based on the cluster-plus-glue-atom model. The HEAs’ coatings were successfully fabricated by laser cladding technology. The microstructure, microhardness, wear resistance and corrosion resistance were measured by a scanning electron microscope, transmission electron microscope, microhardness tester, wear machine and electrochemical workstation, respectively. The experimental results indicate that the phase structures of the [(AlxTi1−x)-(FeCoNi)12](AlxTi1−x)0.5Cr2.5 (x = 0, 0.5, 1) HEA coatings mainly consist of a single face-centered-cubic solid solution and the coatings produce BCC phase with the increase of Ti content. When x = 0, the coating has the highest hardness (402.3 HV0.2) which is 1.92 times that of 904L austenitic super-stainless steel (209.0 HV0.2), the lowest wear volume (0.866 mm3) and the best corrosion resistance. The addition of Ti refined the microstructure of the coatings and promoted the formation of BCC phase, which improved the hardness and wear resistance of the coatings. Considering the wide sources of Ti, Fe and Co elements and the convenience of laser cladding, the coating can provide a cheap protective layer for 904L stainless steel.